Enhancing Students' Speaking Skills in Expression Through the Dubbing Technique - Zainal Abidin; Nurteteng (TEKILA: Journal of Language Teaching and Literature, 2024)
This study investigates the effectiveness of the dubbing technique in enhancing students' speaking skills, particularly in terms of pronunciation, fluency, and overall expression. Conducted with a pre-experimental one-group pretest-posttest design, the research involved nine students from the XII IPA class at SMA Muhammadiyah Al-Amin. Initial assessments indicated that 75% of the participants struggled with accurate pronunciation, leading to issues such as pauses, mumbles, and a lack of fluency. Through a series of dubbing activities, where students imitated native speakers and practiced dialogues within context, notable improvements were observed. Post-intervention results showed significant progress in students' speaking abilities, with enhanced pronunciation accuracy, increased fluency, and greater confidence in expression. The study concludes that the dubbing technique is a valuable tool in language education, offering an engaging and practical approach to improving speaking skills. The findings suggest that incorporating dubbing exercises into language curricula can effectively address common challenges in speaking proficiency, leading to more confident and competent speakers.